Retentionist in chief William Howard Taft and the question of Philippine independence, 1912-1916 - Burns, Adam D. (Quezon City Ateneo de Manila University, 2013)
"Between 1900 and 1913, Republican William Howard Taft maintained a keen interest in preserving a US imperial connection with the Philippines. Following defeat in his presidential reelection campaign of 1912, Taft became the unofficial leader of a "retentionist" movement to stop the US Democratic Party from making any firm promise of future independence for the islands, which he saw as a "policy of scuttle." This article brings light to the underexplored role Taft played in this movement, which proved a marked contrast to the route the US ultimately took in its interventions across the globe in the twentieth century and beyond."
Keywords: Imperialism -- United States; US-Philippine relations; Philippine Independence, 1912-1916.